Initial and boundary value problems for functional integro-differential equations. (1994) - Ntouyas, S. K.; Tsamatos, P. Ch.
Abstract : In this paper, we study initial and boundary value problems for functional integro-differential equations, by using the Leray-Schauder Alternative.